1980
DOI: 10.1111/j.1528-1157.1980.tb04301.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Amygdaloid Kindling by Chronic Pretreatment with Cocaine or Methamphetamine

Abstract: Amygdaloid kindling was induced by daily electrical stimulation in the left amygdala in five groups of cats: a chronic cocaine pretreatment group; a chronic methamphetamine (MAP) pretreatment group; two treatment groups, one using pimozide and the other haloperidol during the period when kindling was being induced; and a drug-free control group. The number of left amygdaloid stimulations required for generalized convulsions was significantly greater in the two chronic pretreatment groups and significantly less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…They reported that the progress of amygdaloid kindling to a generalized seizure in cats could be suppressed by dopamine receptor agonists and facilitated by dopamine receptor antagonists. In another experiment, they (64) reported that cats pretreated with dopamine agonists developed hemiconvulsions instead of symmetric generalized convulsions and lateralized interictal discharges in the kindled hemisphere. On rekindling, seizure development was significantly suppressed, and behavioral responses were enhanced.…”
Section: A Alternative Psychosesmentioning
confidence: 95%
“…They reported that the progress of amygdaloid kindling to a generalized seizure in cats could be suppressed by dopamine receptor agonists and facilitated by dopamine receptor antagonists. In another experiment, they (64) reported that cats pretreated with dopamine agonists developed hemiconvulsions instead of symmetric generalized convulsions and lateralized interictal discharges in the kindled hemisphere. On rekindling, seizure development was significantly suppressed, and behavioral responses were enhanced.…”
Section: A Alternative Psychosesmentioning
confidence: 95%
“…The FIV/cat system has been developed into an animal model for studying lentivirus effects on both the immune and CNS systems (Podell et al, 2000). There are seven main reasons that the FIV/cat system is ideally suited for examining the effects of methamphetamine on the neurological form of the disease: (i) both FIV and HIV-1 are lentiviruses and share many common structural and biochemical properties; (ii) the clinical syndrome for both FIV and HIV-1 is remarkably similar; (iii) from our preliminary work, as well as the contributions of other investigators, the FIV/cat system has been developed into a reproducible disease model, with the establishment of reliable measures (detectable as soon as two months post-infection) of both general and neurological disease progression; (iv) the FIV/cat system is a natural model, dependent upon active virus replication in its natural host; (v) because of the relatively low cost of cats, large numbers of animals can be employed in properly controlled studies, thus, increasing the likelihood of meaningful results being obtained; (vi) specific pathogen free (SPF) cats are available, eliminating confounding interactions with other feline pathogens and (vii) since cats are a species of veterinary importance and are commonly used as experimental animals in neuroscience, the nervous and immune systems of the cat have been well characterized, plus the pharmacology of numerous compounds (including methamphetamine) have been thoroughly investigated in the feline species (Ellinwood and Escalante, 1970;Escalante and Ellinwood, 1970;Sudilovsky et al, 1974;Baker et al, 1976;Balster et al, 1976;Dankova et al, 1977;Fujii et al, 1979;Ishikawa and Yamamoto, 1979;Sato et al, 1980;Sato, 1983;Maeda et al, 1985;Maeda andMaki, 1986, 1987;Emori et al, 1991). Given these numerous advantages of the FIV/cat model, it would be timely to take advantage of this system and apply it towards understanding the effects of drug abuse on lentivirus disease progression.…”
mentioning
confidence: 99%
“…Prior to the initiation of our studies, a review of the literature revealed that cats have frequently been used in methamphetamine studies (Ellinwood and Escalante, 1970;Escalante and Ellinwood, 1970;Sudilovsky et al, 1974;Baker et al, 1976;Balster et al, 1976;Dankova et al, 1977;Fujii et al, 1979;Ishikawa and Yamamoto, 1979;Sato et al, 1980;Sato, 1983;Maeda et al, 1985;Maeda and Maki, 1986;Maeda and Maki, 1987;Emori et al, 1991). The reported doses ranged from 0.04 mg/kg per injection to as high as 50 mg/kg per day (Escalante and Ellinwood, 1970;Balster et al, 1976).…”
mentioning
confidence: 99%
“…36 Furthermore, chronic APZ was reported to improve epileptic disorders in humans, 37 therefore supporting that modifying dopaminergic tone may slow down the development of epilepsy. 38 Given the complex pharmacological profile of APZ, it cannot be ruled out, however, that the effects on other biogenic amines (eg, 5HT) also contribute to the chronic reduction of seizures. 28…”
Section: Da Tone During the Maturation Of The Epileptic Networkmentioning
confidence: 99%